The effects of the COVID-19 pandemic on ICT adoption in Peru - Huarag Guerrero, Enrico Marcel (2020)
This paper aims to analyze the impact of the COVID-19 pandemic in Peru on the adoption and implementation of information and communication technologies. For this purpose, it analyzes the state of implementation of ICT before the pandemic, and the changes that occur to face it, both in the fields of public health management, e-commerce, and telework.